Calling for Compliance. Transnational Advocacy Networks in the Mediterranean Sea. A Case Study on Norm Compliance at Europe’s Liquid Borders - Lindner, Julia (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2021)
The paper observes compliance theories on transnational advocacy networks in the Mediterranean Sea; a multinational border region being widely considered as the “deadliest border” in the world. This situation has led to a measurable “rush to the sea” of organisations which belong to Transnational Advocacy Networks (TAN) or define themselves as “humanitarians”. Part of today’s theory on the impact of transnational advocacy networks is that consistent and continuous engagement of TAN leads to increased norm commitment and even norm compliance in states with strong institutions. However, after the implementation of a system of bilateral treaties (2017 Italy - Libya, 2016 Turkey and European Union (EU)) by the EU, the number of travellers reaching EU soil has significantly decreased. Additionally, changing political circumstances in Libya and internal policies of EU member states have contributed to lowering the number of arrivals.